Biodegradable Polyanhydrides as Encapsulation Layers for Transient Electronics. (9th June 2020) - Choi, Yeon Sik; Koo, Jahyun; Lee, Young Joong; Lee, Geumbee; Avila, Raudel; Ying, Hanze; Reeder, Jonathan; Hambitzer, Leonhard; Im, Kyungtaek; Kim, Jungwon; Lee, Kyung‐Mi; Cheng, Jianjun; et al.
Abstract: Bioresorbable electronic systems represent an emerging class of technology of interest due to their ability to dissolve, chemically degrade, disintegrate, and/or otherwise physically disappear harmlessly in biological environments, as the basis for temporary implants that avoid the need for secondary surgical extraction procedures. Polyanhydride‐based polymers can serve as hydrophobic encapsulation layers for such systems, as a subset of the broader field of transient electronics, where biodegradation eventually occurs by chain scission. Systematic experimental studies that involve immersion in phosphate‐buffered saline solution at various pH values and/or temperatures demonstrate that dissolution occurs through a surface erosion mechanism, with little swelling. The mechanical properties of this polymer are well suited for use in soft, flexible devices, where integration can occur through a mold‐based photopolymerization technique. Studies of the dependence of the polymer properties on monomer compositions and the rates of permeation on coating thicknesses reveal some of the underlying effects. Simple demonstrations illustrate the ability to sustain operation of underlying biodegradable electronic systems for durations between a few hours to a week during complete immersion in aqueous solutions that approximate physiological conditions. Systematic chemical, physical, and in vivo biological studies in animal models reveal no signs of toxicity or other adverse biological responses. Abstract : Synthetic procedures, degradation kinetics, water absorption properties, and water barrier characteristics of bioresorbable polyanhydride are presented. This polymer, as encapsulation layers in water‐soluble electronic devices, can be used to define the functional lifetimes by controlling the coating thickness and polymer chemistry. In vitro permeability encapsulation and in vivo biocompatibility studies support the potential use of this material in temporary biomedical implants with designs for both acute and chronic operation.